Strategi Promosi Tabungan iB Maslahah Dalam Meningkatkan Jumlah Nasabah - Priatna, Pipin; Sutira, Andri (Jurnal Etnik: Ekonomi-Teknik, 2021)
Promotion strategy is the beginning of product introduction to consumers, which is very important because it relates to the benefits that will be obtained by the company. If it is supported by well-structured planning, then the promotion strategy will be very useful. This research is a scientific research with descriptive qualitative research methods, namely research that seeks to decide the division of the current problem based on data, analysis and interpretation, which aims to find theories from the field. The promotional strategy carried out by the Funding Officer for the iB Maslahah Savings product to increase the number of customers, namely: Making offers to campus agencies, schools, and others by picking up the ball. Promotional offers carried out by Funding Officers through social media such as Instagram, WhatsApp and print media such as local newspapers and Bandung radio as well as through the installation of banners located in strategic places. In the promotional strategy for the iB Maslahah savings product at Bank BJB Syariah KCU Bandung, there has been significant growth from the last 3 years with a pick-up and ball promotion strategy as well as through social media Instagram and Whatsapp as well as by installing banners.